Testing for an Economic Gradient in Health Status Using Subjective Data - Lokshin, Michael (2012)
Can self-assessments of health reveal the true health differentials between 'rich' and 'poor'? The potential sources of bias include psychological adaptation to ill-health, socioeconomic covariates of health reporting errors and income measurement errors. We propose an estimation method to reduce the bias by isolating the component of self-assessed health that is explicable in terms of objective health indicators and allowing for broader dimensions of economic welfare than captured by current incomes. On applying our method to survey data for Russia we find a pronounced (nonlinear) economic gradient in health status that is not evident in the raw data. This is largely attributable to the health effects of age, education and location.